THE USE OF CCTV RECORDINGS AS ELECTRONIC EVIDENCE IN MURDER CASES IN THE COURT PROCESS (CASE STUDY OF CASE NUMBER 777/PID.B/2016/PN.JKT.JUNCTO APPEAL DECISION NUMBER 393/PID/2016/PT.DKI JUNCTO CASSATION DECISION NUMBER 498/K/PID/2018 JUNCTO PK DECISION NUMBER 69 PK/PID/2018) - Charles Roy Saut Martua Sijabat; Timbo Mangaranap Sirait (Adisam Publisher, 2025)
The use of CCTV recordings as electronic evidence in criminal murder cases, the conclusions of which are as follows: First, that the regulation of the use of CCTV (Closed Circuit Television) recordings, which are electronic evidence, as circumstantial evidence in criminal law enforcement, as stipulated in Law Number 8 of 1981 concerning Criminal Procedure Law (KUHAP) Article 188 paragraph (1), where circumstantial evidence is an act, event or circumstance which, due to its consistency, either between one another or with the criminal act itself, indicates that a criminal act has occurred and who the perpetrator is. However, because evidence can only be obtained from witness statements, letters, and statements from the accused, the Indonesian Criminal Justice System adheres to the stelsel negatief wettelijk, whereby only evidence that is valid according to the law can be used for proof. This means that outside of these provisions, CCTV (Closed Circuit Television) cannot be used as valid evidence in such cases. Second, that in terms of legal interpretation, CCTV (Closed Circuit Television) recordings, which are electronic evidence, are circumstantial evidence in Case Number 777/Pid.B/2016/Pn.Jkt.Pst Juncto Appeal Decision Number 393/PID/2016/PT.DKI Juncto Cassation Decision Number 498/K/Pid/ 2018 Juncto PK Decision Number 69 PK/Pid/2018, because the CCTV (Closed Circuit Television) was not taken directly by the investigator, but by an unauthorised person, witness Dermawan Salihin, who went directly to Olivier Restaurant and took the CCTV USB (Closed Circuit Television), which was then seized by the police, the electronic evidence was not obtained lawfully. Furthermore, in criminal cases, because the Indonesian criminal procedural law system adopts the Stelsel negatief wettelijk system, where only evidence that is lawful according to the law can be used for proof, and the collection of evidence must be done lawfully, then because during the trial process, information was obtained from witnesses presented in the criminal case that the CCTV footage was taken by someone who was not authorised to do so, it can be legally interpreted that the CCTV footage cannot be used as evidence or as circumstantial evidence.